Friday
March 24, 2017

Post a New Question

Posted by on .

Prove that sin^2(Omega) - Cos^2(Omega) / tan(Omega) sin(Omega) + cos(Omega) tan(Omega) = cos(Omega) - cot (Omega) cos (omega)

  • Trigonometry - ,

    I substituted any angle in the equation the way you typed it, and the equation was false.
    I then tried it as

    (sin^2 Ø - cos^2 Ø)/(tanØsinØ + cosØtanØ)

    using Ø instead of omega for easier typing.

    and got
    LS = (sinØ+cosØ)(sinØ-cosØ)/(tanØ(sinØ+cosØ)
    = (sinØ - cosØ)/(sinØ/cosØ)
    = cosØ(sinØ - cosØ)/sinØ
    = cosØsinØ/sinØ - cos^2 Ø/sinØ
    = cosØ - (cosØ/sinØ)cos‚
    = cosØ - cotØcosØ
    = RS

  • Trigonometry - ,

    What does LS and RS stand for?

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question